Qualitative evaluation of primary care providers’ experiences caring for frequent users of the emergency department - Catherine Hudon; Patrick Bodenmann; Nicolas Senn; Mary Malebranche; Olivier Hugli; Laureline Brunner; Marina Canepa Allen; Francis Vu; Christina Akré (BMJ Open)
Objectives Many interventions have been developed over the years to offer frequent users of the emergency department (FUEDs) better access to quality coordinated healthcare. Despite recognising the role primary care physicians (PCPs) play in FUEDs’ care, to date their perceptions of case management, the most studied intervention, have rarely been assessed. Furthermore, a gap regarding PCPs’ experience of caring for FUEDs persists. Thus, this study aimed to explore PCPs’ perceptions of the care provided to FUEDs in emergency and primary care settings, their views on the local case management team (CMT), and their suggestions to improve FUEDs’ care.Design Qualitative study using in-depth semistructured interviews and inductive thematic analysis.Setting Canton of Vaud, Switzerland.Participants Thirty PCPs participated, 16 in private practice (PP-PCPs) and 14 based at the Lausanne University Centre of General Medicine and Public Health (Unisanté—U-PCPs).Results U-PCPs and PP-PCPs thought that most FUEDs’ emergency department (ED) visits were legitimate, but questioned ED adequacy to meet FUEDs’ needs. Yet, both PCP groups reported encountering many challenges in FUEDs’ care themselves. In this context, PP-PCPs seemed more satisfied of the care they provided to FUEDs than U-PCPs. Generally, U-PCPs seemed to find more value in the CMT to help them care for FUEDs than PP-PCPs. To enhance FUEDs’ care, U-PCPs and PP-PCPs suggested enhancing collaboration with other healthcare providers. U-PCPs also wished to increase their availability, and some PP-PCPs considered outpatient clinics, larger group practices or medical centres most appropriate to handle FUEDs’ needs.Conclusions This study highlights the many challenges PCPs face in caring for FUEDs, that a CM intervention has the potential to mitigate, and provides ways forward in improving FUEDs’ care, including reinforced communication with the CMT and ED physicians, and structural changes to their own way of delivering care to FUEDs.